2014
DOI: 10.1016/j.jhealeco.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Removing financial barriers to organ and bone marrow donation: The effect of leave and tax legislation in the U.S.

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 50 publications
4
41
0
1
Order By: Relevance
“…At the time of this writing, 35 states had passed legislation to offer tax deductions or credits, or other benefits, to living organ donors (34). These programs vary state by state, are underused, and are of unknown effectiveness.…”
Section: Indirect Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of this writing, 35 states had passed legislation to offer tax deductions or credits, or other benefits, to living organ donors (34). These programs vary state by state, are underused, and are of unknown effectiveness.…”
Section: Indirect Costsmentioning
confidence: 99%
“…Fifteen of these living organ donor tax laws function as deductions (and therefore require the LKD to itemize taxes to use them), which may affect the utility of tax relief for low-income earners. Comprehensive reviews of these types of legislation found no statistically significant effect on organ donation for paid-leave legislation or for tax credits or deductions (34,35). However, the effect of this legislation on LKD financial burden (as opposed to donation rates) has not been studied.…”
Section: Indirect Costsmentioning
confidence: 99%
“…In addition, although many states offer tax deductions or credits for living donors who incurred expenses, many transplant providers and living donors are unaware that these programs exist. Tax relief programs have not affected rates of LDKT and LKD, perhaps because they require itemization of taxes (75,76). Because lower-income donors, who would benefit most from tax relief related to LKD expenses, are least likely to itemize tax returns, we recommend that all states consider establishing a tax credit (versus deduction) based on actual costs incurred by donors.…”
Section: Recommendation 1: Remove Financial Disincentives To Lkdmentioning
confidence: 99%
“…They hypothesize that the statistically indistinguishable effects may stem from low cash value of the tax deduction to defray costs faced by donors, lack of public awareness and a depletion of organ donor pools in the pre-legislation period. Lacetera et al (2014) find significant effects for bone marrow but not other organs. Boulware et al (2008) find that state legislation and federal policies are not associated with living related or overall donations.…”
Section: Introductionmentioning
confidence: 74%